Synaesthesia and individual differences - Rogowska, Aleksandra Maria (Cambridge University press, 2017)
"Synaesthesia is a fascinating cognitive phenomenon where one type of stimulation evokes the sensation of another. For example, synaesthetes might perceive colours when listening to music, or tastes in the mouth when reading words. This book provides an insight into the idiosyncratic nature of synaesthesia by exploring its relationships with other dimensions of individual differences. Many characteristics of linguistic-colour synaesthetes are covered including personality, temperament, intelligence, creativity, emotionality, attention, memory, imagination, colour perception, body lateralization and gender. Aleksandra Rogowska proposes that linguistic-colour synaesthesia can be considered as an abstract form of a continuous variable in the broader context of cross- and intra-modal associations. There has been a resurgence of interest in synaesthesia and this book will appeal to students and scientists of psychology, cognitive science and social science, and to those who are fascinated by unusual states of mind"--